PENGARUH PERMAINAN TRADISIONAL CANG CERICIT TERHADAP BAHASA EKSPRESIF ANAK USIA DINI DI KOTA PONTIANAK - Kholifah Kholifah; Marmawi Rais; Andini Linarsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractAt an early age, children's language development is included in the expressive language phase. Children use expressive language because they are already able to express their thoughts, opinions and feelings through spoken language. This expressive language will make it easier for children to communicate and adjust to their environment. This research aims to find out the influence of Traditional Cang Cericit Games on Early Childhood Expressive Language Skills in Kemala Bhayangkari Kindergarten 13 Pontianak Kota. The research method used is quantitative with the Pre Experimental Designs approach with the form of One Group Pretest-Posttest Designs. The source of this research is all B4 graders at Kemala Bhayangkari Kindergarten 13 Pontianak Kota. The research instruction is using observation sheets and chek lists. This research data collection technique is observation and documentation. Based on the results of data analysis and hypothesis testing, the study showed that there was an influence of traditional Cang Cericit games on children's expressive language skills in class B4. This is evidenced by the results of SPSS calculations with the wilcoxon signed ranks test formula, obtained z value of -2,521 and Asymp. Sig. (2-tailed) of 0.012, because a significant value (0.012) < the value of α (0.05), so ????0 it is rejected and ???????? accepted. So it can be said that the influence of tradiisonal game Cang Cericit on the expressive language skills of early childhood in Kemala Bhayangkari Kindergarten 13 Pontianak Kota.Keywords: Early Childhood, Expressive Language, Traditional Games